HUBUNGAN ANTARA TINGKAT PENGETAHUAN DENGAN PERILAKU CUCI TANGAN PEKERJA PADA PENGRAJIN BATIK SEMBUNGAN - Warseno, Agus; Dwi Utami Sejati, Mutiara (MEDIA ILMU KESEHATAN, 2017)
Background: Batik is the one of the Indonesian’s heritage which uses color barrier technique in which wax is used as a tool to draw the design applied on the surface of a cloth. Batik artisan is one of the occouptions that requires the use of chemical subtances such as wax and dye. Since they are often exposed by chemical subtances, they may have skin problem. Thetefore, hand washing behavior becomes one of preventive action for skin and digestive problems. Objective: To identified the correlation between knowledge level and hand washing behavior in the work environment of batik artisans in Sembungan, Gulurejo, Lendah, Kulon Progo. Methods: This study was a quantitative research using correlative design study and using cross sectional approach. Total sampling was used to collect 30 respondents. The result was analyzed using Gamma with the level of significancy p<0,05. Results: The result of the study showed majority of the level of knowledge on hand washing was high level for 70% and 53,3% respondents have a good behavior on hand washing. The result of statistical test showed p-value 0.016<0.05with correlation coeficient 0.674 which had a strong correlation. Conclusion: There was a corelation between knowledge level on hand washing and hand washing behavior in work environment of batik artsisans in Sembungan, Gulurejo, Lendah, Kulon Progo. Keywords : Knowledge, batik artisans, hand washing behavior.